Racially and ethnically diverse women leading education a world view - Watson, Terri N.; Normore, Anthony H. (Advances in educational administration ;, 2016)
This book's primary focus is on racially and ethnically diverse women in educational leadership. Each chapter is written from a unique conceptual or empirical lens as shared by international female leaders. Of particular interest to readers is the ingenious pairing of contributors for optimum scholarship, whereby the majority of chapters are co-authored by at least one male in a leadership role who shares in the crusade for social, cultural, political, and economic gender and racial equality for effective leadership that works. The general content is framed by but not limited to theoretical frameworks such as Black / Feminist Thought, Critical Race Theory, and Leadership for Social Justice. The chapters range from a critical examination of global society and cross-cultural collaboration, to the intersection of race, law, and power. Each chapter illuminates the lives and experiences of racially and ethnically diverse women in leadership positions in a diverse range of educational settings and contexts.